From the Market to the Home: Objects and Their Trade Between History and Archaeology (Northern Italy, 1275–1500) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
This contribution aims to analyze the commercial landscape and the circulation of objects in northern Italy from the late 13th to the 15th century. The perspective presented here arises from the intersection of historical and archaeological sources. Lombardy is characterized by its vibrant commercial activity and favorable political conditions, such as the reduction of transaction costs under the Visconti. However, interpreting economic transformations requires careful consideration of the limitations of the available sources. Written sources, such as customs records, provide valuable yet partial data on the quantity and types of traded objects, often distorting the reality of daily consumption. Similarly, archaeological evidence, despite showing an exponential increase in material visibility between the 13th and 15th centuries, does not always allow for precise reconstruction of economic flows. An integrated analysis of written and material sources is therefore essential to understand the complexity of late medieval commerce. The research also focuses on Valtellina, a strategic area for trade between the Po Valley and Northern Europe. Archaeological data, particularly concerning ceramics, are crucial but do not always correspond to the information derived from customs records, highlighting the necessity of interdisciplinary approaches for an accurate study of medieval markets.
Keywords: Trade; Late Middle Ages; Alps; Lombardy; Tolls; Material Culture